Are female orphans at risk for early marriage, early sexual debut, and teen pregnancy?: Evidence from Sub-Saharan Africa - Palermo, Tia; Peterman, Amber (Wiley, 2009)
Female orphans are widely cited as being at risk for early marriage, early childbearing, and risky sexual behavior; however, to date no studies have examined these linkages using population‐level data across multiple countries. This study draws from recent Demographic and Health Surveys from ten sub‐Saharan African countries to examine the relationship between orphanhood status and measures of early marriage, early sexual debut, and teen pregnancy among adolescent girls aged 15 to 17. Results indicate that, overall, little association is found between orphanhood and early marriage or teen pregnancy, whereas evidence from seven countries supports associations between orphanhood and early sexual debut. Findings are sensitive to the use of multivariate models, type of orphan, and country setting. Orphanhood status alone may not be a sufficient targeting mechanism for addressing these outcomes in many countries; a broader, multidimensional targeting scheme including orphan type, schooling, and poverty measures would be more robust in identifying and aiding young women at risk.